2022
DOI: 10.1021/acs.joc.1c03155
|View full text |Cite
|
Sign up to set email alerts
|

HFIP-Promoted Selective Hydroxyalkylation of Aniline Derivatives with Arylglyoxal Hydrates

Abstract: A HFIP-promoted highly selective hydroxyalkylation of aniline derivatives with arylglyoxal hydrates has been realized. The reaction produces various N,N-dialkylanilines and their derivatives with α-hydroxy carbonyl units in good to excellent yields under mild conditions. Furthermore, the synthetic potential of this method has been demonstrated by the facile synthesis of several structurally interesting molecules such as benzil, 1,2,4-triazine, quinoxaline, hydantoin, and 2-thiohydantoin with aromatic amine uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…On the basis of the forementioned results and previous literature, , a plausible mechanism was proposed (Scheme ). Initially, intermediate I is formed by anion exchange of [Cp*RhCl 2 ] 2 with AgSbF 6 and carboxylic acid via Cl – extraction.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…On the basis of the forementioned results and previous literature, , a plausible mechanism was proposed (Scheme ). Initially, intermediate I is formed by anion exchange of [Cp*RhCl 2 ] 2 with AgSbF 6 and carboxylic acid via Cl – extraction.…”
mentioning
confidence: 89%
“…An elaborate strategy is exploring the one-pot synthesis of 6H-benzo[c]-chromen-6-ol via tandem C−H activation, which could construct C−C bond via nucleophilic substitution to provide benzo[c]chromenes under mild conditions. 8 In 2017, the Cui group developed a rhodium-catalyzed tandem C−H activation of benzamides with diazonaphthalen-2(1H)-ones for the synthesis of lactones. 9 Recently, the Samanta group disclosed a similar methodology by using ruthenium as the catalyst (Scheme 1C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that HFIP can be used to promote the generation of a C-C bond by cleavage of a C-O bond (the substrates of aromatic aldehyde hydrate, propar-gyl alcohol, difluoroacetaldehyde ethyl hemiacetal, etc.) via the Friedel-Crafts alkylation pathway [26][27][28][33][34][35]. Based on the properties of HFIP and the above-mentioned control experimental results, a plausible mechanism of HFIP-promoted Friedel-Crafts alkylation was put forward (Scheme 3).…”
Section: Mechanism Investigationmentioning
confidence: 99%
“…To synthesize the required pyrrolyl diol derivatives 1 and 2 , we utilized the hydroxyalkylation of pyrroles with glyoxals. We followed the procedure described by Ren et al, involving the reaction of pyrroles with arylglyoxals in the presence of HFIP as a promoter . The readily obtained pyrrol-2-yl α-acyloins S1a-j were then treated with alkynyl organometallics to produce pyrrol-2-yl glycols 1 .…”
mentioning
confidence: 99%